Bloomsbury CPD library : independent learning - Taylor, John L. (London : Bloomsbury, 2018)
Independent learning is an ideal which many teachers aspire to but find difficult to achieve. It is common for school inspectors to comment on the need for students to learn more independently, and from higher education admissions officers and employers there is a constant call for students to be better equipped to be able to learn and think for themselves. Students themselves enjoy and benefit from lessons in which they are given the opportunity to begin to take charge of the learning process, particularly when there is space for them to explore and inquire into topics that grab their attention. At the same time, there is enormous pressure on schools to 'teach to the test', leading many teachers to feel that they have to play safe and cannot risk giving their students genuine responsibility for their own learning, lest results suffer. Critics also argue that students need to be taught directly, as the capacity for meaningful inquiry is not one that most students possess, and even when it is present, the open-ended nature of the inquiry process can make learning inefficient. In this book, John L. Taylor shows how the rhetoric about independent learning can be turned into a practical reality. The book explores the foundations of effective learning and demonstrates how it is possible to implement an approach to learning which encourages students to learn to think for themselves. It shows how by teaching students to think better, teachers can ensure that they both succeed in jumping assessment hurdles and also enjoy a richer, more meaningful educational experience."--Publisher's description
Includes bibliography and index.
Keywords: Self-culture.; Independent study; EDUCATION / Administration / General